Effect of Maternal Anaemia on Neonatal Anthropometry: A Cross Sectional Study - Shankar, Vishaka; Karthik S, Karthik S; Krishnappa J, Krishnappa J; Srikanth, Channakeshvala (Journal of Neonatal Surgery, 2025)
Introduction:As per the WHO, hemoglobin of less than 11g in Pregnancy is considered as Anemia.This study was designed to study the effect of maternal anemia on neonatal anthropometry. Materials and Methods:A cross sectional study was conducted at a tertiary care hospital in Karnataka with an objective to find the effect of maternal anaemia on neonatal anthropometry. The inclusion Criteria was term mothers aged between 18-35 years with singleton gestation and having anaemia as per WHO definition. The mothers with medical conditions except anaemia like TORCH infection, smokers, alcoholics, known diabetes mellitus and hypertension before pregnancy, Haemoglobinopathies and who received blood transfusion were excluded. Under aseptic precautions, 5ml peripheral vein-puncture blood sample was collected from the pregnant mothers and haemoglobin was estimated. Birth weight ,Length and head circumference were measured using a non-stretchable tape. Results :A total of 120 term mothers and neonates were included. 60 mothers were in anemic group and 60 were in non-anemic group. On comparing of various neonatal anthropometries with babies born to anemic and non-anemic mothers, it was found that the maternal anemia had statistically significant effect on birth weight, length and mid arm circumference of the neonates. They were significantly lower in babies born to anemic mothers than in babies born to non-anemic mothers. Conclusion: The present study concludes that the maternal anemia had statistically significant effect on birth weight, length and mid arm circumference of the neonates. Hence appropriate intervention can prevent the deleterious effect of anemia on neonatal growth..